REVALUASI ASET TETAP : SUDUT PANDANG PMK No. 191/PMK.010/2015 DAN RELEVANSI NILAINYA - Hapsari, Indah; Murdiawati, Dewi (Jurnal Riset Akuntansi dan Keuangan, 2018)
Abstract. This study aims to provide empirical evidence regarding the success of PMK No.191/PMK.010/2015 revaluation of fixed assets and also test the value relevance of its accounting information. The research sample is a banking sector company listed on the Indonesia Stock Exchange during 2014-2016. Analytical techniques used to determine the success of PMK No. 191 / PMK.010 / 2015 is McNemar Test, and multiple linear regression tests by emphasizing the explanatory power of the Feltham and Ohlson models to test the value relevance of the accounting information content. Based on the results of McNemar Change Test, it can be concluded that there are differences in method selection of fixed assets at the time before and after the implementation of PMK No.191/PMK.010/2015. Meanwhile, the information presented at fair value have a value relevance of its accounting information.Â Â Â